TEKNIK PEREKATAN BAHAN KULIT ATASAN SEPATU DENGAN BAHAN KARET MENGGUNAKAN METODE SPRAY - Suharyanto Suharyanto (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2016)
Gluing method with spray that the layer of glue is thin and flat is done in order to save glue and increase gluing quality as well as save the time. Dilution formula is 75 ml added with 150 ml diluent or a ratio of 1 than 2, or in percent 50% compared to 100%; with diluent using thinner, a volatile substance bringing the glue into gluing area in which it can be attached as the diluent evaporates. Data results show that 5 minutes drying time is 0.06407 N, 6 minutes 0.05002 N, 7 minutes 0.04446 N, N 0.03661 8 minutes and 9 minutes 0.02092 N. From the table and graph made, a good adhesive is glue with drying time of 5 minutes, then 6 minutes, 7 minutes, 8 minutes, and 9 minutes. From the results of research, it reveals that using sprayer is more efficient and effective, easy to use, showing good results, and saving time.